Effects of the addition of high‐temperature water on the bubble structure, rheological properties, and sensory characteristics of gluten‐free rice flour bread. Issue 12 (6th October 2022) - Saito, Kumiko; Okouchi, Maya; Yamaguchi, Mana; Takechi, Tayori; Hatanaka, Yoshiro; Kitsuda, Koji; Mannari, Takayo; Takamura, Hitoshi
Abstract: This study investigated the effect of hot water on the rheological properties of the batter, bubble structure, and sensory properties of the bread. We focused on the thickening effect of starch gelatinization and developed a method to produce gluten‐free rice flour bread without additives by increasing the temperature of the water used in the production of gluten‐free rice flour bread. Hot water at 50–80°C was more effective than 5°C in improving bubble number and bubble size. In batters prepared using water at 68 and 70°C, which had excellent bubble structure, the frequency‐dependent fluctuations of the storage and loss moduli were smaller, while the loss coefficient values were larger. The batters showed more favorable sensory qualities at higher temperatures than the cold‐water batters. Appropriate temperature control of the water added during batter preparation can enable easier and cost‐effective preparation of high‐quality gluten‐free rice flour bread. Novelty impact statement: Appropriate temperature control of the water added during batter preparation improved the quality of gluten‐free rice flour bread. Batter prepared with water at 68 and 70°C improved rheological properties, bubble structure, and sensory properties significantly.